Managing rural development with small farmer participation - Bryant, Coralie (Kumarian Press ConnecticutUS, 1984)
Examines ways in which small farmer programs and projects can be increased. Presents the view that participatory development is difficult to design and implement and identifies strategies for effective development and coordination of the participatory process.